Enrichment of Rice Grains with Zinc through Agronomic Bio-fortification - Gayatri Goswami, Sukritee Hazarika, D. Bhattacharyya and B.K. Medhi, N.Gogoi, A. Basumatary (Journal of the Indian Society of Soil Science, 2017)
A field experiment was carried out at instructional-cum-research farm of Assam Agricultural University, Jorhat, Assam to enrich grains of some popular high yielding rice varieties with soil and soil plus foliar application of zinc (Zn). Three different levels of Zn viz., 0, 21 kg ha-1 as soil application, and 21 kg ha-1 as soil application + foliar spray of 0.5% of ZnSO4 thrice at heading, flowering and panicle initiation stages were evaluated. Irrespective of varieties, highest mean Zn concentration of 29.3 mg kg-1 was observed in rice grain with soil + foliar application of Zn. The mean Zn content varied from 17.6 to 34.2 mg kg-1 and it increased from 5.8 to 20.3 per cent over control with soil application and 13.2 to 32.3 per cent with soil + foliar application of Zn. Amongst the varieties, the highest concentration was found in variety Kushal (34.3 mg kg-1) followed by Moniram (33.5 mg kg-1). Variety Kushal also recorded highest Zn uptake (140.9 g ha-1) followed by the variety Ranjit (127.1 g ha-1). However, in terms of Zn use efficiency and apparent Zn recovery efficiency, varieties Moniram and Ranjit, respectively performed best. Thus, Ranjit recorded the highest Zn accumulation efficiency by grains over other varieties.